Miljöcertifiering i ett subarktiskt klimat - Huuva, Christopher (Umeå universitet, Institutionen för tillämpad fysik och elektronik, 2017)
Today there is a comprehensive urban transformation going on in Kiruna and Malmberget. The two towns need to be moved to continue mining iron ore. The first building in the new centre in Kiruna is a new city hall named Kristallen. To build more sustainable and to secure that the building fulfils high standard within energy, indoor climate and built with good materials and quality, the municipality of Kiruna has the ambition to certify Kristallen with Miljöbyggnad level Silver. The purpose with this thesis has been to increase the knowledge of certification with Miljöbyggnad in a subarctic climate. To understand how Kristallen fulfils the requirements in Miljöbyggnad, documents including simulation- and calculation results has been collected and analysed. People that have been working with the project was interviewed in order to examine if Kiruna and its subarctic climate has meant some difficulties with the certification with Miljöbyggnad. The results of this study shows that some of the interviewed persons experienced some difficulties to fulfil the requirements for indicator solar heat load, fraction of energy carriers, thermal climate summer and daylight. The difficulties were considered mostly because of the solar insolation and the midnight sun that occur during the summer period in Kiruna. All of the interviewed people experienced that the certification resulted in higher building costs but agreed that Kristallen fulfils high standard within energy, indoor climate and quality. Miljöbyggnad is a complex subject that is depending on many factors when deciding if the certification results in higher building costs, added values for the building or difficulties with the certification. This study shows experienced difficulties and factors that results in higher building costs for just one building in a subarctic climate. Therefore, more studies about certification with Miljöbyggnad in similar climate should be done to decide if the climate or a buildings design is the reason for the experienced ...